Effects of high energy on steel structure in deformation - Savenko, Vladimir S.; Troitskiy, Oleg A.; Hrushchov, Mikhail M.; Stashenko, Vladimir I.; Zernitsa, Denis A. (Journal of the Belarusian State University. Physics, 2020)
The author of the article investigates how microwave radiation affects the processes of active deformation and mechanical stress relaxation in stressed stainless steel specimen under the electric current and when vector E (of microwave radiation) moves in different directions along the axe of the specimen. When vector E of microwave radiation was oriented in a longitudinalis way and electric current was passed, the softening of metal increased from 22 to 30 %. Multi-criteria analysis of steel samples with electric current and samples with no electric current was made. Analysis findings showed that external energy deposition influenced greatly on deformation of steel crystals. The action of high-density electric current pulses and microwave radiation on a sample loaded above the yield strength increases the ductility of stainless steel, and its strength characteristics, the microstructure is modified. Phase composition of steel was also investigated. The studies showed that the content of martensitic and austenitic phases in steel changed significantly. Moreover, the results showed that there was an additional mechanism of electroplastic deformation in the crossed fields of microwave radiation and magnetic field of current.